The Analysis of Occupational Safety and Health of the Batik Industry - Junaidi, Mar’atul Sholihah; Fatoni, Rois; Fatimah, Siti (Advance Sustainable Science, Engineering and Technology, 2020)
Occupational safety and health is an important issue in an operational process, both in traditional and modern sectors. Prevention of work accidents can be done by knowing the risks that exist in a process, one of them is through Hazard Identification, Risk Assessment, and Risk Control (HIRARC) methods. In the batik industry, batik makers come into direct contact with materials containing hazardous chemicals and uncomfortable work positions. In addition, the craftsmen also do not care for the environment and do not use personal protective equipment. The purpose of this study is to determine the factors of occupational safety and health. This purpose also to use of personal protective equipment while working and identify potential hazards in the batik production process in the batik industry of Sekar Arum and Mahkota Laweyan. Factors causing occupational accidents include an unsafe batik environment, unsafe equipment, containing hazardous substances and unsafe work attitudes. In addition, the lack of orderly use of personal protective equipment in the form of boots, gloves and aprons. Based on the findings of the hazard, it is known that there are hazards with low category namely in the nyanting room, washing and drying rooms, and the waste management room with hazard percentage is 10,26 %, medium category namely in the stamp room with hazard percentage is 30,77 % and high category namely the coloring room with hazard percentage is 38,46 %.